Seasonal dynamics of submarine groundwater discharge in Zhanjiang Bay: an investigative study utilizing 222Rn as a tracer - Lin, Xin; Chen, Xiao; Chen, Fajin; Jin, Guangzhe; Wang, Chao; Mayakrishnan, Machendiranathan; Shi, Ziyang; Si, Xiangcheng (Frontiers in Marine Science, 2024)
The spatial and temporal variation of submarine groundwater discharge (SGD) has been a topic of interest for researchers in recent years. However, the study of SGD is limited within the scope of Zhanjiang Bay. The present study examined the fluctuation patterns of seawater 222Rn in Zhanjiang Bay during the period from June 2021 to March 2022. This investigation employs the 222Rn tracing technique to establish a mass balance model to compute the SGD rate, and assess the significance of SGD in translocating nutrients into the bay. The Zhanjiang Bay is located in western Guangdong Province, known for its high temperatures and typhoon vulnerability. We conducted a four-month sampling, observing the differences between the rainy and dry seasons. Precipitation exerts a significant influence on the seasonal variations of SGD. The SGD rates of Zhanjiang Bay ranged from 7.14 to 10.75 cm·d-1 in the dry season and from 13.38 to 14.61 cm·d-1 in the rainy season. SGD-derived nutrients also exhibited seasonal fluctuations, the annual input of nutrients it supplies may be comparable to the quantity delivered by rivers, which significantly impacted the trophic status of the bay.